Removal of bisphenol A by adsorption mechanism using PES–SiO2 composite membranes. Issue 15 (2nd August 2016) - Muhamad, Mimi Suliza; Salim, Mohd Razman; Lau, Woei Jye; Hadibarata, Tony; Yusop, Zulkifli
ABSTRACT: Polyethersulphone (PES) membranes blended with silicon dioxide (SiO2 ) nanoparticles were prepared via a dry-jet wet spinning technique for the removal of bisphenol A (BPA) by adsorption mechanism. The morphology of SiO2 nanoparticles was analysed using a transmission electron microscopy and particle size distribution was also analysed. The prepared membranes were characterized by several techniques including field emission scanning electron microscopy, Fourier transform infrared spectroscopy and water contact angle. The adsorption mechanism of membrane towards BPA was evaluated by batch experiments and kinetic model. The influence of natural organic matter (NOM) in feed water on membrane BPA removal was also studied by filtration experiments. Results showed that BPA adsorption capacity as high as 53 µg/g could be achieved by the PES membrane incorporated with 2 wt% SiO2 in which the adsorption mechanism was in accordance with the pseudo-second-order kinetic model. The intraparticles diffusion model suggested that the rate limiting factor of membrane adsorption mechanism is governed by the diffusion of BPA into the membrane pores. The presence of 10 ppm NOM has reported to negatively reduce BPA removal by 24%, as it tended to compete with BPA for membrane adsorption. This work has demonstrated that PES–SiO2 membrane has the potential to eliminate trace amount of BPA from water source containing NOM.